Testing the Validity and Reliability of the Step Test for Elderly Balance - Ramadani, Ardhita Dyah; Kurniawati, Dwi; Utomo, Budi (Poltekkes Kemenkes Surakarta, 2023)
Background: A common problem among the elderly is a decline in functional capacity, which can affect their balance and lead to a high risk of falling. Balance is the ability to maintain body position while stationary or moving. Maintaining balance in the elderly is important to enable them to remain independent in performing various daily activities. The Step Test is one of the measurement tools that can be used to determine the level of balance in the elderly. The purpose of this study was to determine the validity and reliability of the Step Test in measuring balance in the elderly by comparing it with the Berg Balance Scale (BBS). Methods: This study used a descriptive research design with an observational method involving 20 elderly subjects. Results: Based on the validity test, p=0.001 and r=0.689 were obtained, which means that there is a strong relationship between the Step Test and the Berg Balance Scale (BBS). The interrater reliability test yielded a result of p=0.000 and ICC=0.897, while the intrarater reliability test yielded a result of p=0.000 and ICC=0.881. Conclusion: The Step Test is proven to be valid and reliable for measuring balance in the elderly. The Step Test is recommended for use in detecting the risk of falling more quickly and accurately in the elderly.